Hospitales familiares y comunitarios. Relato de una experiencia local. - Cárcamo Saldaña, Juan Pablo (Cuadernos Médico Sociales, 2025)
Family and Community Hospitals (FCH) are essentially Primary Care Establishments that, nevertheless, provide services throughout the entire hospital cycle. FCHs emerged under the umbrella of the National Health System in the mid-20th century and became the main institution for addressing health problems demanded in the rural municipalities where they are located. Health management, the relationship with their environment, and with the community are the themes presented in this article, which aims to share an experience that opens spaces for reflection and discussion about healthcare practices. These practices should not only consider the highly demanded box-based medical attention, but also the ongoing analysis of needs and available resources in order to deliver responses that are equitable and relevant, even when resources are scarce--an issue that requires ingenuity and the creation of ways to move forward and find solutions. In this context, the formation of teams and process-oriented work is fundamental to organizing the supply and adapting it to demand.